European principles of care for physiotherapy provision for persons with inherited bleeding disorders: Perspectives of physiotherapists and patients. Issue 4 (4th May 2022) - de Kleijn, Piet; Duport, G.; Jansone, K.; Marinić, M.; McLaughlin, P.; Noone, D.; Ramishvili, L.; Tollwé, A.; Stephensen, D.; ,
Abstract: Introduction: In their Chronic Care Model, the World Health Organisation states that people with chronic disorders and their families should be informed about the expected course, potential complications, and effective strategies to prevent complications and manage symptoms. Physiotherapists are a key professional group involved in the triage, assessment and management of musculoskeletal conditions of persons with a bleeding disorder (PWBD). Nevertheless, recent reports describe access to physiotherapy for those with these conditions is only sometimes available. Aim: Access to high quality individualised physiotherapy should be ensured for all PWBD, including those with mild and moderate severities, male and female, people with von Willebrand Disease (vWD) and other rare bleeding disorders. Physiotherapy should be viewed as a basic requisite in their multidisciplinary care. Methods/ results: Following a series of meetings with physiotherapists representing the European Association for Haemophilia and Allied Disorders (EAHAD) and PWBD representing the European Haemophilia Consortium (EHC) and a review of publications in the field, eight core principles of physiotherapy care for persons with a bleeding disorder have been co‐produced by EAHAD and EHC. Conclusion: These eight principles outline optimum standards of practice in order to advocate personalised patient‐centred care for physical health in which both prevention and interventions include shared decision making, and supported self‐management.